The Impact of Using Laser and Milling Techniques to Create Zirconia Patterns on Streptococcus oralis Biofilm Formation - Neusa Silva; Joana Marques; João Caramês; Filipe Silva; António Mata; Mariana Brito da Cruz (Ceramics)
This study aimed to evaluate zirconia dental implant surfaces patterned using Nd:YAG laser or conventional milling techniques against Streptococcus oralis adhesion and biofilm formation. Zirconia dental implant discs were subjected to surface patterning treatments and categorized into four groups: groove texturing by conventional milling (GM), pore texturing by conventional milling (PM), groove texturing by Nd:YAG laser (GL), and pore texturing by Nd: YAG laser (PL). Streptococcus oralis CECT 907T was cultivated on enriched blood agar plates and then transferred to a brain–heart infusion modified medium and incubated at 37 °C under anaerobic conditions until reaching the exponential growth phase. The bacterial suspension was then seeded on 24-well plates containing the treated discs. The viability of bacteria within the biofilm was determined based on colony-forming unit (CFU) counts, while the total biofilm was quantified by measuring its biomass. A qualitative analysis was conducted using scanning electron microscopy (SEM) images to evaluate the bacterial morphology. The statistical analysis of multigroup comparisons was performed using Kruskal–Wallis test with post hoc pairwise comparison, as well as Mann Whiney U test, with significance set at p < 0.05. After both 1 h and 24 h of incubation of Streptococcus oralis on the discs, all groups showed similar results, with no statistically significant differences (p > 0.05). A comparison of the Nd: YAG laser-treated surfaces with conventionally milled surfaces, as well as grooves versus pores for CFU counts, also revealed no statistically significant differences (p > 0.05) for both 1 h and 24 h of culture. Biomass quantification at both the 1 h and 24-h time points showed similar results across the groups, without statistical differences. When comparing the conventionally machined surfaces to Nd: YAG laser-treated surfaces in terms of biomass, no significant differences were observed (p > 0.05). Similarly, the comparison between groove-patterned surfaces and pore-patterned surfaces showed no statistically significant difference. The groove and pore patterns on zirconia surfaces with Nd: YAG laser or conventional milling did not change the Streptococcus oralis adhesion and biofilm formation behavior. Additional studies are recommended to expand our knowledge in this area.